Synthesis of CdSe/ZnS Nanoparticles with Multiple Photoluminescence - Sliusariak, T. K.; Andriichuk, Y. M.; Vojtovych, S. A.; Zhukovskyi, M. A.; Khalavka, Y. B. (Physics and Chemistry of Solid State, 2020)
The CdSе/ZnS nanostructures of Core-Shell type, that have multi-wave emission, are described and a scheme of possible energy transitions in the studied system is presented. CdSe nuclei were synthesized by mixing cadmium and selenium precursors without creating an inert atmosphere. The cadmium complex with sulphanilamide was used as a cadmium precursor and simultaneously as a stabilizing ligand. To grow the shell, zinc stearate and thiourea were gradually added to the solution of cadmium selenide nuclei in octadecene at 200°C. TEM studies show that the obtained CdSe/ZnS nanoparticles have the shape close to tetrahedral with an effective diameter up to 10 nm. The thickness of the ZnS shell is about 3-4 nm. From the absorption spectra of the CdSe/ZnS nanoparticles, it is clear that the shell growth leads to a sharp increase in the absorption in the short wavelentgh area, which means the formation of a wide gap ZnS material. The obtained CdSe/ZnS nanostructures emit three fluorescence peaks in the visible range. They are attributed to exciton transitions in the nucleus, recombination at defects of the boundary between the core and the shell, and recombination at defects of the shell. Such property provides CdSe/ZnS nanocrystals with a wide range of functionalities.